GAMBARAN POLA MAKAN PADA PENDERITA HIPERTENSI YANG MENJALANI RAWAT INAP DI IRNA F RSUD SYARIFAH AMBAMI RATO EBU KABUPATEN BANGKALAN – MADURA - Choirun Anisah; Umdatus Soleha (Universitas Nahdlatul Ulama Surabaya, 2014)
An appropriate diet is a stylist to consider by people with hypertension because it will greatly help control blood pressure. Surveys in 5 patients with hypertension are known 2 of them know about the diet to fit patients with hypertension, 3 the rest did not know about the diet to fit patients with hypertension. The purpose of this study was to know the description of the diet in patients with hypertension. The design of this study is descriptive. Entire population of hypertension patients hospitalized in Hospital Syarifah IRNA F Ambami Rato Ebu Bangkalan Madura by 20 people. The sample of 20 respondents using the technique of saturated samples. Variable is the diet in patients with hypertension. The collection of primary data using a questionnaire, analysis of data by frequency distribution tables and the way the process is editing, coding, scoring and tabulation are adjusted to the standard assessment. Results showed that most respondents 70% (14 respondents) inappropriate diet hypertension diet and nearly half of respondents 30% (6 respondents) have an appropriate diet hypertension. Research conclusion is that most respondents have a diet that is not appropriate diet hypertension. For that is expected for health care providers can provide information to patients with hypertension, about an appropriate diet for patients with hypertension.